MADRASAH PRINCIPAL MANAGEMENT IN IMPROVING SCHOOL COMPETITIVENESS IN AL HIKMAH PALEMBANG ELEMENTARY SCHOOL - Hepriyanti, Lisa; Amilda, Amilda; Nurlaila, Nurlaila (STAI Asy-Syukriyyah, 2025)
The management of the head of the madrasah in increasing the competitiveness of schools at Madrasah Ibtidaiyah Palembang is very necessary as a direction to be carried out so that the competitiveness of the school is achieved. Supporting the success of the head of the madrasah in increasing the competitiveness of this school is by striving for a well-organized, precise and systematic implementation management process and in accordance with applicable policies. This study aims to describe and analyze how the planning, organization, implementation and supervision of the madrasah head management in improving school competitiveness in Madrasah Ibtidaiyah Al Hikmah Palembang. The method used in this study is a qualitative descriptive method whose data collection includes interviews, observations and documentation with research informants, namely the head of the madrasah as the key informant and teachers and education staff as supporting informants. The results of this study show that 1) The planning of madrasah heads in increasing school competitiveness at Madrasah Ibtidaiyah Al Hikmah Palembang by carrying out several meeting activities related to PPDB, independent curriculum training for teachers, quality of facilities, programs for madrasas and regular monthly meetings between madrasah heads of teachers and education staff as an effort to increase school competitiveness. 2) The organization of the head of the madrasah in increasing the competitiveness of the school at Madrasah Ibtidaiyah Al Hikmah Palembang, namely in terms of the division of duties and authority, is decided and approved directly by the head of the madrasah together with the teachers and education staff at the meeting held before the new school year begins, the head of the madrasah has divided the task in the form of an organizational structure in accordance with the competence or expertise possessed by each teacher or existing education personnel. 3) The implementation of the head of the madrasah in increasing the competitiveness of the school at Madrasah Ibtidaiyah Al Hikmah Palembang is running quite smoothly, especially the interest of the community is very closely related to increasing the competitiveness of the school because in the implementation of the interest of the community, Madrasah Ibtidaiyah Al Hikmah makes a school program that is believed to be able to attract the interest of the community, namely not imposing the Education Development Contribution (SPP) money for every month. 4) The supervision of the head of the madrasah in improving the competitiveness of the school at Madrasah Ibtidaiyah Al Hikmah Palembang is carried out by the head of the madrasah with monitoring and evaluation related to the quality of educators, quality of facilities, school achievements and community interest. This is done so that they can find out what needs to be improved or improved again so that the school's competitiveness can increase